Market-level effects of firm-level adaptation and intermediation in networked markets of fresh foods: A case study in Colombia. (February 2018) - Mejía, Gonzalo; García-Díaz, César
Abstract: This paper presents a multi-agent simulation that studies market competition in a multi-stage negotiation with both direct sales and intermediation, in the presence of cost heterogeneity at the agent (i.e., producer) level. Producers sell their products according to an adaptive reinforcement strategy. Product is sold to clients (small shops and consumers) according to two types of marketplaces, which are characterized by whether they obtain the product from intermediaries or directly from producers. The model is applied to the case of a networked market of potato ( Solanum tuberosum ) producers in Bogotá, Colombia, and calibrated to real data. The results reveal that, contingent upon the number of producers, number of intermediaries, unit transportation cost and producers' culture, intermediation might lead to greater traded quantities than sales through farmers' (local) markets. Also, we found that increasing the intensity of competition among intermediaries is at odds with the increase of producers' long run profit. Thus, we conclude that intermediation still plays an important role to maintain the supply ecosystem, especially when transportation costs are important in a network of isolated and fragmented network of producers. Highlights: A multi-agent simulation to study intermediation in fresh food supply chains. Consideration of learning effects in the agent model. Discussion on policies that aim to eliminate intermediation.